Formulation and Evaluation of Fast Dissolving Tablets of Diclofenac Sodium Using Different Superdisintigrants by Direct Compression Method - Modi, Amit (International Journal of Pharmaceutical & Biological Archive, 2012)
Formulation and Evaluation of Fast Dissolving Tablets of Diclofenac Sodium Using Different Superdisintigrants by Direct Compression Method